Fuzzy Logic-based Input Evaluation Method for Interactive 2D Animation Scene Design using Computer Vision - Shi, Xiaobo (Informatica, 2025)
Two-dimensional (2D) interactive animation engages the user to command and communicate with the design using touch and pointer functions. The user input delegates specific tasks for the design replicated on the screen through precise detection. This article introduces an Input Evaluation for Design-Specific Function (IE-DSF) method to improve the response precision of the 2D models. The user input through touch or devices is evaluated for sensitivity and design region for receiving commands. Based on the difference between input and response time and input region variations, the monotonous response of the design is computed. This computation is fuzzified for its unanimity throughout different input sequences. In this process, fuzzy logic-based validation is employed to determine minimum and maximum response time from the sequence of 2d design interaction. The maximum variation is used to improve the design sensitivity, and the minimum variation is used to increase the design functions on the screen. Therefore, the different recommendations correlate with providing frame-based 2D sequences with precise computer vision technology. The variation changes are reverted in the independent frames without modifying the entire design. This feature improves the consistency and evaluation of various interactive designs. The proposed IE-DSF method achieved a significant improvement of 9.38% in consistency, an 11.31% reduction in response time, and an enhanced interaction response of 8.8% across various inputs. With a considerable decrease in design modifications, reducing them by 11.1% helps optimize 2D animation design interactions.